Career Opportunities in Agriculture and Allied Sciences - Rana, N.; Agnihotri, M. K.; Chetti, M. B.; Rathore, N. S. (Indian Farming, 2018)
The opportunities are available to work as research scientist, teacher, Marketing Manager, science writer, Quality Control Officer or production in-charge in the food, chemical and pharmaceutical industry, Analyst (Venture-Capitalist) Environmental /Safety Specialist. Biotechnology companies require corporate executives with business/ management degrees. A graduate in biotechnology can get a job in government sector such as universities and colleges, research institutes or at private centers as research scientist/assistant.